Estimating the Cost of Preeclampsia in the Healthcare System: Cross-Sectional Study Using Data From SCOPE Study (Screening for Pregnancy End Points). Issue 6 (December 2017) - Fox, Aimée; McHugh, Sheena; Browne, John; Kenny, Louise C.; Fitzgerald, Anthony; Khashan, Ali S.; Dempsey, Eugene; Fahy, Ciara; O'Neill, Ciaran; Kearney, Patricia M.
Abstract : To estimate the cost of preeclampsia from the national health payer's perspective using secondary data from the SCOPE study (Screening for Pregnancy End Points). SCOPE is an international observational prospective study of healthy nulliparous women with singleton pregnancies. Using data from the Irish cohort recruited between November 2008 and February 2011, all women with preeclampsia and a 10% random sample of women without preeclampsia were selected. Additional health service use data were extracted from the consenting participants' medical records for maternity services which were not included in SCOPE. Unit costs were based on estimates from 3 existing Irish studies. Costs were extrapolated to a national level using a prevalence rate of 5% to 7% among nulliparous pregnancies. Within the cohort of 1774 women, 68 developed preeclampsia (3.8%) and 171 women were randomly selected as controls. Women with preeclampsia used higher levels of maternity services. The average cost of a pregnancy complicated by preeclampsia was [Euro sign]5243 per case compared with [Euro sign]2452 per case for an uncomplicated pregnancy. The national cost of preeclampsia is between [Euro sign]6.5 and [Euro sign]9.1 million per annum based on the 5% to 7% prevalence rate. Postpartum care was the largest contributor to these costs ([Euro sign]4.9–[Euro sign]6.9 million), followed by antepartum care ([Euro sign]0.9–[Euro sign]1.3 million) and peripartum care ([Euro sign]0.6–[Euro sign]0.7 million). Women with preeclampsia generate significantly higher maternity costs than women without preeclampsia. These cost estimates will allow policy-makers to efficiently allocate resources for this pregnancy-specific condition. Moreover, these estimates are useful for future research assessing the cost-effectiveness of preeclampsia screening and treatment.